Evolutionary Pro‐To‐Thr Mutation in the Intrinsically Disordered Domain of ANP32 Family Members Modulates Their Target Binding Modes - Blanca Baños‐Jaime; Ana B. Uceda‐Mayo; Francisco Rivero‐Rodríguez; Miguel Á. Casado‐Combreras; Alejandro Velázquez‐Cruz; Adrián Velázquez‐Campoy; Laura Corrales‐Guerrero; Miguel A. De la Rosa; Irene Díaz‐Moreno (Advanced Science)
Abstract Gene duplication has allowed protein evolution toward novel functions and mechanisms. The differences between paralogous genes frequently rely on the sequence of disordered regions. For instance, in mammals, the chaperones ANP32A and ANP32B share a common evolutionary line and have some exchangeable functions based on their similar N‐terminal domains. Nevertheless, their C‐terminal low‐complexity‐acidic‐regions (LCARs) display substantial sequence differences, unveiling some degree of variability between them, in agreement with their different tissue‐specific expression patterns. These structural and computational results indicate that a substitution in the vicinity of the nuclear localization signal (NLS), of Pro in ANP32A for Thr in ANP32B, determines the overall compactness of the C‐terminal LCAR. The different structural properties of the disordered region affect the binding mode of ANP32 members to their targets. This type of divergent binding mode is exemplified with the extra‐mitochondrial cytochrome c (Cc), a well‐known ANP32B partner and which now determine also binds to ANP32A; and with the RNA binding protein HuR, whose export to the cytoplasm is mediated by ANP32 proteins under stress. Therefore, differential expression patterns of ANP32A or ANP32B may affect the regulation of Cc and HuR and can help to explain the distinct roles of these proteins in diseases.